Presencia de Mosquitero Común (Phylloscopus collibyta) y Mosquitero Ibérico (Philloscopus Ibericus) en la provincia de Salamanca = Presence of Common Chiffchaff (Phylloscopus Collybita) and Iberian Chiffchaff (Phylloscopus Ibericus) in the province of Salamanca - Ceballos Barbancho, Antonio (Polígonos. Revista de Geografía, 2012)
El principal objetivo del presente trabajo es determinar la presencia de mosquitero común (Phylloscopus collybita) y mosquitero ibérico (Phylloscopus ibericus) en la provincia de Salamanca durante el período reproductor. Para ello se realizaron un total de 78 transectos lineales en hábitats potencialmente favorables para ambas especies. Los resultados obtenidos demuestran la presencia de ambas especies en la provincia de Salamanca, pero de forma escasa, puntual y dispersa, siempre en zonas con un ombroclima sub-húmedo/húmedo o en bosques de ribera azonales con un microclima específico. The major objective of the present work is to determine the presence of Common Chiffchaff (Phylloscopus collybita) and Iberian Chiffchaff (Phylloscopus ibericus) during the breeding season in the province of Salamanca. For this, a total of 78 linear tran- sects were carried out in potential and favourable habitats for both species. The main results show the spatial occurrence of the two species in the province of Salamanca. This is, however, scarce, sporadic and spatially dispersed, both in areas under sub-humid/humid ombroclimatic conditions and in azonal riparian forest with specific microclimatic conditions.